Avian magnetoreception: elaborate iron mineral containing dendrites in the upper beak seem to be a common feature of birds. - Gerald Falkenberg (Public Library of Science (PLoS), 2010)
The magnetic field sensors enabling birds to extract orientational information from the Earth's magnetic field have remained enigmatic. Our previously published results from homing pigeons have made us suggest that the iron containing sensory dendrites in the inner dermal lining of the upper beak are a candidate structure for such an avian magnetometer system. Here we show that similar structures occur in two species of migratory birds (garden warbler, Sylvia borin and European robin, Erithacus rubecula) and a non-migratory bird, the domestic chicken (Gallus gallus). In all these bird species, histological data have revealed dendrites of similar shape and size, all containing iron minerals within distinct subcellular compartments of nervous terminals of the median branch of the Nervus ophthalmicus. We also used microscopic X-ray absorption spectroscopy analyses to identify the involved iron minerals to be almost completely Fe III-oxides. Magnetite (Fe II/III) may also occur in these structures, but not as a major Fe constituent. Our data suggest that this complex dendritic system in the beak is a common feature of birds, and that it may form an essential sensory basis for the evolution of at least certain types of magnetic field guided behavior.